Ease and Difficulty in L2 Phonology: A Mini-Review - Archibald, John (Frontiers in Communication, 2021)
A variety of phonological explanations have been proposed to account for why some sounds are harder to learn than others. In this mini-review, we review such theoretical constructs and models as markedness (including the markedness differential hypothesis) and frequency-based approaches (including Bayesian models). We also discuss experimental work designed to tease apart markedness versus frequency. Processing accounts are also given. In terms of phonological domains, we present examples of feature-based accounts of segmental phenomena which predict that the L1 features (not segments) will determine the ease and difficulty of acquisition. Models which look at the type of feature which needs to be acquired, and models which look at the functional load of a given feature are also presented. This leads to a presentation of the redeployment hypothesis which demonstrates how learners can take the building blocks available in the L1 and create new structures in the L2. A broader background is provided by discussing learnability approaches and the constructs of positive and negative evidence. This leads to the asymmetry hypothesis, and presentation of new work exploring the explanatory power of a contrastive hierarchy approach. The mini-review is designed to give readers a refresher course in phonological approaches to ease and difficulty in acquisition which will help to contextualize the papers presented in this collection.